New Zealand Lost Cases: Case Note: R v E Hipu - Dorsett, Shaunnagh (Victoria University of Wellington Law Review, 2010)
This note considers the 1845 decision of the Supreme Court of New Zealand in E Hipu. E Hipu was the first decision of the Supreme Court to apply those provisions of the Native Exemption Ordinance which allowed a fine to be substituted for imprisonment in cases of theft. The Native Exemption Ordinance was a significant mechanism in the early colony by which criminal law was modified in its application to Maori, and was crucial to the framing of Crown-Maori relations.